Research on Steelmaking-Continuous Casting Production Scheduling Problem Based on Augmented Lagrangian Relaxation Algorithm under Multi-Coupling Constraints. Issue 1 (2019) - Sun, Liangliang; Jin, Hang; Yu, Yaqian; Li, Zhi; Xi, Jiali
Abstract: Steelmaking - continuous casting production scheduling is an important part of steelmaking production system. A scientific and reasonable steelmaking - continuous casting production scheduling is the key to improve the production efficiency of the steelmaking - continuous casting production system. In this paper, with the shortest total charge waiting time and the castings that are processed on time as the optimization goal, with the charges that are casted continuous within same casting and machine capacity constraints and so on as the constraints to established a mixed integer programming mathematical model. The augmented Lagrangian relaxation algorithm is used to solved the scheduling problem. The diagonal quadratic approximation method is used to linearize quadratic term so that it can be transformed into a problem to be solved with separable structure. Experiments show that the algorithm proposed has the advantages of fast convergence and short solution time for solving the steel-continuous casting scheduling problem compared to the traditional Lagrange algorithm, and the superiority is more obvious when the scale of the problem is increased.